Study the effect of colchicine administration on Reducing the incidence of atrial fibrillation after coronary bypass surgery - دله باسل; مضر عبد اللطيف; باسم معروف (Latakia University Journal -Medical Sciences Series, 2024)
Background : Post-coronary atrial fibrillation (POAF) is a common complication and is associated with high morbidity and mortality rates. The incidence of POAF depends on the patients’ comorbidities and the type of surgery, with an incidence of up to (36-65%) in coronary bypass and valve surgery, (30-40%) after valve surgery, and (30%) after coronary bypass surgery alone Atrial fibrillation usually occurs within (48-72 hours) after surgery. Objectives : Studying the effectiveness of giving colchicine in reducing the incidence of atrial fibrillation following coronary heart surgery using extracorporeal circulation Materials and methods : The research sample included 80 patients admitted to the Department of Cardiac Surgery for elective isolated coronary surgery at Tishreen University Hospital in Lattakia during the time period 2022-2023. The investigators investigated the inclusion criteria in the research . The inclusion criteria All patients admitted to the Department of Cardiac Surgery for elective isolated coronary surgery are between 40-80 years old. Exclusion criteria Complex and emergency surgeries. Patients with chronic atrial fibrillation and atrial flutter The size of the atrium is greater than 60 mm The systolic function of the left ventricle is less than 35% Absence of kidney or liver disease Second and third degree sinoatrial node blockade Patients placed on antiarrhythmics other than beta blockers Patients who have undergone previous coronary bypass surgery Results : We observed a lower incidence of AF after CABG surgery in patients in the colchicine group (3 patients) by 7.5%, compared to the placebo group (9 patients) by 22.5% . Conclusion : Having atrial fibrillation is considered one of the major challenges facing both the doctor and the patient after performing various cardiac surgeries (CABG, valve replacement or repair, repair of congenital heart defects). The risks and side effects resulting from developing AF after these surgeries, which include a prolonged recovery period, increased costs and burdens of care and treatment, and a high incidence of strokes and death, make it necessary to continue research and investigation to find the optimal method for reducing the incidence of AF. (AF). In short, there is a need for more studies and research to know the mechanism of the occurrence of (AF) after heart surgery, and thus to reach effective treatment that prevents or reduces the incidence of (AF) after these surgeries